SOCIAL MEDIA COMMUNICATION AFFECTING BRAND EQUITY IN THAI AUTOMOTIVE INDUSTRY - Jeambua, Katawoot; Pasunon, Prasopchai; Sombultawee, Kedwadee (RMUTT Global Business and Economics Review, 2022)
The objectives of this research were to study the effect of the social media communication affecting the brand equity in Thai automobile industry and to study the harmony of a model of a model of social media communication affecting the brand equity in Thai automobile industry. The research applied quantitative methodology. The sample are the individuals aged 15-65 years with experience in social media communication in automobiles as well as know and have a fondness for automobile/automotive brands. This was comprising of 280 samples. The quantitative data were statistically analyzed, including percentage, arithmetic mean, standard deviation, and the relationships between the independent variables, Pearson’s correlation, and structural equation modeling (SEM). The study revealed that the model, improved and developed by the researcher, was in harmony with the empirical data with Chi-Square = 1,600.825, df = 1,219, P-Value = 0.000, Chi-Square/df = 1.313, CFI = .968, GFI = .830, AGFI = .801, RMSEA = .034 Furthermore, social media communication has direct effect on the brand equity and has indirect effect on the brand equity passing through customer engagement at 0.05 statistically significant level.